Typification of three names of Brazilian Prosthechea (Orchidaceae: Laeliinae) - Vieira, Tiago Luiz; van Den Berg, Cássio (Phytotaxa, 2020)
In the present paper we provide lectotypifications for the names Prosthechea bohnkiana, P. carrii, and P. elisae, and epitypes for the first two. These typifications were necessary due to gross disagreement between the available specimens and the data provided by the authors in the protologues of these names.